Investigating the Antarctic origin of Meltwater Pulse 1A - Coulon, Violaine; Pattyn, Frank (2017)
During the last glacial termination, a phase of abrupt global sea-level rise called Meltwater Pulse 1A took place around 14 500 BP. Although the timing and the magnitude of this event have become better constrained, a causal link between the MWP-1A and an accelerated ice loss from the Antarctic ice sheet has still not been proven. Understanding the origin of this meltwater pulse is of the highest importance when considering the current uncertainty surrounding a potential collapse of the Antarctic ice sheet in response to present-day climate change.We simulated the evolution of the Antarctic ice sheet over the last 40 kyr using the ice-sheet model f.ETISh (Pattyn, 2017). A large ensemble of 54 runs is used to calibrate the model to modern and geologic data and determine a best-fit simulation. Moreover, a sensitivity analysis is carried out to assess the conditions for the occurrence of significant melting of the Antarctic ice sheet. With the best-fit simulation, the influence of an accentuated oceanic melting coincident with Meltwater Pulse 1A is tested to evaluate the likely contribution of Antarctica to this event. For the Antarctic ice sheet to have made a meaningful contribution to the Meltwater Pulse 1A, a sufficient sea-level equivalent ice volume must have existed at the Last Glacial Maximum. Then, this ice volume must have been discharged at the correct time and at a rate fast enough to contribute to this rapid sea-level rise (Golledge et al. 2014).Results reveal that a sufficient ice volume has existed at the Last Glacial Maximum in Antarctica. However, abrupt rises in seal-level and air temperatures, characteristic of the last glaciation termination, do not, on their own, trigger rapid retreat of the modelled ice sheet. For the Antarctic ice sheet to have made a meaningful contribution to the Meltwater Pulse 1A, a specific interaction between the ice sheet and its surrounding ocean – independent of the atmospheric forcing - seems to be necessary. More specifically, rates of freshwater flux from the ...